The Effect of Probiotics on High Fiber Diet in Rumen Fermentation Characteristics. (March 2019) - Sari, N F; Ridwan, R; Rohmatussolihat,; Fidriyanto, R; Astuti, W D; Widyastuti, Y
Abstract: The productivity of cattle must be achieved through feed efficiency which has strong correlation with the rumen work. The efforts to increase productivity of cattle can use probiotics as feed additive in animal feeding. Probiotics are increasingly used in commercial animal production operations to profitably alter the gastrointestinal flora, thus improving animal health and productivity. This study aimed to investigate the effects of different type of probiotics on high fiber diet in live weight change, rumen fermentation, the total rumen of bacteria, and the total of lactic acid bacteria. Three fistulated cattle received a daily ration 2% from body weight (DM) of Pennisetum purpureum (70% of DM), concentrates (30% of DM), and mineral mix (1% of DM). The experiment was arranged as a crossover design with six treatments and three sampling periods as replications. The treatments were (R0) control diet, (R1) control diet + 10 mL of Lactobacillus plantarum TSD-10 per day, (R2) control diet + 10 mL of L. plantarum MX-16 per day, (R3) control diet + 10 mL of L. brevis SPCE-39 per day, (R4) control diet + 10 mL of mix Lactobacillus plantarum TSD-10, L. plantarum MX-16, and L. brevis SPCE-39 per day, (R5) control diet + 10 mL of commercial probiotics per day. Neither pH nor the total of lactic acid bacteria (LAB) were significantly affected by the treatment. Among others treatment, R3 showed a tendency body weight gain. The total of rumen bacteria was affected significantly for R2, R3, R4, and R5 compared with R0. The acetate to propionate ratio were affected for R3, R4, and R5, but were not affected significantly for R2 and R3 compared with R0. The butyrate ratio and rumen ammonia concentration were not affected by the treatment. In conclusion, probiotics change the population of the rumen bacteria. In addition, based on metabolism characteristics, particularly on propionate production and C2/C3 ratio, R3 was shown the best probiotics candidate on high fiber diet. Nevertheless, the difference pattern in volatile fatty acid indicates that different mechanisms may be involved.